1995
DOI: 10.1097/00000542-199501000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Differential Sensory Nerve Block after Lidocaine Spinal Anesthesia 

Abstract: Differential sensory block during spinal anesthesia is due to different recovery profiles of A beta, A delta, and C fibers. Return of A beta current perception thresholds to baseline correlated with duration of surgical anesthesia as assessed with an electrical stimulation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
1
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(76 citation statements)
references
References 13 publications
5
69
1
1
Order By: Relevance
“…CST testing in animal models thus seems comparable to conventional nociceptive testing for the evaluation of local anesthetic effect. During reversible nerve block induced by spinal anesthesia in humans, larger diameter nerve fibers recover more rapidly from anesthesia (Fink, 1989), where recovery profiles for cold sensation (C), pain by pin prick (A␦), and tactile sensation (A␤) correspond to those of individual CPTs at 5, 250, and 2000 Hz, respectively (Liu et al, 1995). Our study of rats receiving 2% lidocaine, in which blockade was reversible in all cases, likewise demonstrated that CSTs for lower frequency stimulation took longer to return to baseline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CST testing in animal models thus seems comparable to conventional nociceptive testing for the evaluation of local anesthetic effect. During reversible nerve block induced by spinal anesthesia in humans, larger diameter nerve fibers recover more rapidly from anesthesia (Fink, 1989), where recovery profiles for cold sensation (C), pain by pin prick (A␦), and tactile sensation (A␤) correspond to those of individual CPTs at 5, 250, and 2000 Hz, respectively (Liu et al, 1995). Our study of rats receiving 2% lidocaine, in which blockade was reversible in all cases, likewise demonstrated that CSTs for lower frequency stimulation took longer to return to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by stimulation using three sine wave pulses at frequencies of 2000, 250, and 5 Hz, which in humans stimulate large myelinated (A␤), small myelinated (A␦), and small unmyelinated sensory fibers (C), respectively (Pitei et al, 1994). Some investigators have applied CPT measurements to the evaluation of differential sensory blockade following spinal or epidural anesthesia (Liu et al, 1995;Tay et al, 1997;Sakura et al, 1998). Although CPT testing represents an established method in humans, only one report has described the application of CPT in animal studies (Kiso et al, 2001).…”
mentioning
confidence: 99%
“…This is especially relevant, as C fibres are presumed to respond optimally to both low frequency (5 Hz) electrical current and cold stimuli. 9 Furthermore, it may be possible through further study to determine a percent increase in CPT that correlates with loss of cold sensation. The results presented here suggest that a peripheral nerve stimulator can be used at low frequency to obtain CPT with acceptable reproducibility; however, since most commercially available peripheral nerve stimulators can be set to a frequency of 1 Hz or 2 Hz (but not 5 Hz), it is likely to be more clinically relevant to consider using these frequencies when planning future studies.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Also, stimulation of the sural nerve with an electric current has been used to assess epidural fentanyl injection. 11 Peripheral nerve stimulators, which are commonly used for locating nerve structures, can also facilitate transcutaneous stimulation via adhesive gel pads or a percutaneous electrode guidance probe, 12 but these devices have not been well studied for measuring CPT.…”
Section: Résumémentioning
confidence: 99%
“…It is known that current perception threshold (CPT) testing can evaluate sensory nerve fibers in both a quantitative and selective manner: CPTs at 2000, 250 and 5 Hz stimuli directly represent the functions of Aβ, Aδ and C fibers, respectively [5,6].…”
Section: Introductionmentioning
confidence: 99%